Construction and Building Research - Llinares-Millán, Carmen; Fernández-Plazaola, Igor; Hidalgo-Delgado, Francisco; Martínez-Valenzuela, María Montserrat; Medina-Ramón, Francisco Javier; Oliver-Faubel, Inmaculada; Rodríguez-Abad, Isabel; Salandin, Andrea; Sánchez-Grandia, Rafael; Tort-Ausina, Isabel (Springer Netherlands : Imprint: Springer, 2014)
Many areas of knowledge converge in the building industry and therefore research in this field necessarily involves an interdisciplinary approach. Effective research requires strong relations between a broad variety of scientific and technological domains and more conventional construction or craft processes, while also considering advanced management processes, where all the main actors permanently interact. This publication takes an interdisciplinary approach grouping various studies on the building industry chosen from among the works presented for the 2nd International Conference on Construction and Building Research. The papers examine aspects of materials and building systems; construction technology; energy and sustainability; construction management; heritage, refurbishment and conservation. The information contained within these pages may be of interest to researchers and practitioners in construction and building activities from the academic sphere, as well as public and private sectors.